USTADZ ABI AZKAKIA'S DA'WAH: Analysis of the content of messages in the Mobile Legends game on Instagram - Fajri Syah, Nurcholis (Universitas Islam Madura, 2025)
Social media is one of the effective means of spreading the message, including in the context of Islamic da'wah, various platforms such as Instagram have allowed preachers to reach a wider audience. One of the preachers who utilizes this technology is Ustadz Abi Azkakia who creatively combines da'wah messages with popular games. This research aims to analyze da'wah messages packaged through social media. This study uses a qualitative approach with a content analysis method. Data was collected through non-participant observation of the content of posts on Instagram accounts. The results of the study show that he is able to package da'wah messages in an attractive style and in accordance with the daily life of game players. These messages emphasized the importance of maintaining a sportsmanship, avoiding negative behaviors such as toxic gaming, and reminding people of religious obligations that must still be fulfilled, even in the midst of busy playing games. By utilizing a platform that is favored by the younger generation, this da'wah becomes easier to accept and understand. Utilize Instagram and Mobile Legends as effective media to spread Islamic values in a contextual, relevant, and attractive manner to young audiences. This research shows that da'wah through Mobile Legends on Instagram is effective in conveying Islamic messages digitally. This approach increases the involvement of the younger generation in understanding Islamic values through popular and interactive media.